Neutrality-based effective tax rates - Deborah Knirsch (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2002)
Effective tax rates (ETRs) are designed to indicate the influence of taxes on investments. Existing ETR models fail to generate ETRs that can be compared to a constant yardstick and to other ETRs. This paper develops a new ETR approach based on neutral tax systems. Integration of neutral taxation into the computation of ETRs overcomes the problem of traditional numerical concepts: Comparison of the new ETR and the statutory tax rate as a constant yardstick reveals preferential or discriminatory taxation of investments. Moreover, the comparison of different ETRs displays which investment is distorted to a higher or lower degree.
urn:nbn:de:bsz:21-opus-18841
Keywords: H21; H25; H32; 330; Effective Tax Rate; Neutral Tax System; Tax Distortion; Investment; Steuerbelastung; Besteuerungsgrundsatz; Investition; Theorie